Characteristics of patients assisted at an ambulatory of dementia from a university hospital Perfil dos pacientes atendidos no ambulatório de demência de um hospital universitário - Lyssandra dos Santos Tascone; Rita de Cássia G. Marques; Elaine Cristina Pereira; Cássio M.C. Bottino (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To present socio-demographic characteristics, mean scores of tests and scales applied to patients with dementia and discuss the relationship between test scores, clinical diagnoses and the severity of dementia. METHOD: Patients (n=113) were diagnosed according to the DSM-IV criteria, and the diagnostic work-up included physical and neurological examination, auxiliary exams, cognitive and functional tests, and the evaluation of neuropsychiatric symptoms. RESULTS: Mean age was 74.0 years. Alzheimer's disease (AD) was diagnosed in 62.8% of the patients, AD and vascular dementia in 8.8%, other dementias in 14.2%, and mild cognitive impairment in 2.7%. At least one neuropsychiatric symptom was diagnosed in 96.9% of the sample. There were significant differences on cognitive and functional performance between the groups classified according to dementia severity. CONCLUSION: Neuropsychiatric symptoms were quite common in patients with dementia, being more frequent as severity increased, and those symptoms were associated with functional impairment in the patients. OBJETIVO: Apresentar características demográficas, escores médios de testes e escalas aplicadas aos pacientes com demência e discutir a relação dos escores dos testes com os diagnósticos clínicos e a gravidade da demência. MÉTODO: Pacientes (n=113) foram diagnosticados segundo os critérios para demência do DSM-IV, avaliados com história clínica, exame físico, exames complementares e aplicação de testes cognitivos, funcionais e neuropsiquiátricos. RESULTADOS: A idade média foi 74,0 anos. A doença de Alzheimer (DA) foi diagnosticada em 62,8% dos casos, DA e demência vascular em 8,8%, outras demências em 14,2%, e comprometimento cognitivo leve em 2,7%, Ao menos um sintoma neuropsiquiátrico foi diagnosticado em 96,9% da amostra. Houve diferenças significativas nos escores dos testes cognitivos e escalas funcionais entre os grupos classificados segundo a gravidade de demência. CONCLUSÃO: Sintomas neuropsiquiátricos são muito comuns, mais freqüentes em casos graves, e estes sintomas estão associados ao comprometimento funcional nos pacientes com demência.